(untitled) (Bangladesh Journal of Botany, 2022)
Meloidogyne graminicola (nematode) mostly attacks young roots of plants; hence, age of host becomes a predominant factor in infection and pathogenesis. A pot experiment was conducted in the net house condition during kharif, 2018 in complete randomized design to find out the changes in growth and yield parameters of rice cv. Naveen due to inoculation of M. graminicola at different plant age. The nematode infested rice plants showed chlorosis, stunting and characteristic terminal galls on the roots which ultimately resulted in severe reduction in growth, unfilled spikelets, reduction in tiller development and other growth attributes over control. Nematode inoculation at early crop stage retarded the plant growth and yield attributes by reducing the rice yield up to 57.4%. The maximum percentage of reduction in plant height (19.8%), tiller number (39.6%), dry weight of shoot (43.6%), dry weight of root (45.6%) and total biomass (49.6%) was observed in the plants inoculated at two weeks after sowing. Bangladesh J. Bot. 51(3): 411-416, 2022 (September)